Desain Pengembangan Laboratorium Dakwah: Studi Kasus UIN Walisongo Semarang - Riyadi, Agus (Jurnal Komunikasi Islam, 2019)
Abstract: This article is the result of a descriptive qualitative research report in the laboratory of the Da'wah and Communication Faculty, Walisongo State Islamic University (UIN), Semarang. This study has concluded that the design of the Da'wah laboratory at the Da'wah and Communication Faculty of UIN Walisongo Semarang was developed based on the department, which included the Islamic Community Development Laboratory (PMI), the Islamic Communication and Broadcasting Laboratory (KPI), the Da'wah Management Laboratory (MD), the Guidance and Islamic Counseling Laboratory (BPI) In addition, the laboratory development is in line with university Tridharma. The laboratory development phase is carried out through four stages, namely the initiation phase and the construction of a quality management system, the optimization phase of academic support capabilities, the intensification and extensification phase of research services, and the external capacity building phase.